Comparative analysis of methods for estimating genetic parameters of fruit-quality traits in apple breeding program - Catalina Pinto; Carlos Maldonado; Raffaele Testolin; Guido Cipriani; Gloria De Mori (Euphytica, 2025)
Apples, originating from Central Asia, are widely cultivated worldwide, with China producing 47.6 million tonnes annually. Despite their global importance, breeding programs often focus on a limited number of high-quality cultivars, potentially threatening genetic diversity. To mitigate this risk, advanced statistical methods could be employed to improve selection strategies. For example, the multi-trait BLUP method, which accounts for genetic correlations among traits, can reduce selection bias but increases computational complexity due to the model’s intricacy and slow convergence of the REML process. Bayesian methods, like Markov Chain Monte Carlo (MCMC), offer a solution to these challenges. This study compares single-trait and multi-trait approaches using REML/BLUP and MCMC/BLUP to estimate variance components and predict genetic values. Over two seasons, phenotypic data from 304 seedlings and 16 parents were analyzed using an animal model to predict their genetic values related to fruit quality traits. Significant progress was made in estimating genetic parameters and selecting parents for traits such as fruit weight, flesh firmness, and soluble solids content in the University of Udine’s apple breeding program. The multi-trait BLUP method improved the accuracy of predicted breeding values, particularly for fruit weight, polar diameter, flesh firmness, and soluble solids content. The multivariate repeated measures model, despite low correlations between some trait pairs, was recommended for integrating multi-season results and accounting for trait correlations. The Bayesian MCMC approach proved superior in genetic evaluations, offering higher heritabilities and genetic gains compared to Fisherian methods (REML). It effectively handles small sample sizes, captures more genetic variance, and enhances breeding value predictions, recommending traits like fruit size, firmness, and sweetness for selecting superior parents.

Genetic and ploidy diversity of pear (Pyrus spp.) germplasm of Friuli Venezia Giulia, Italy - Irina Baccichet; Serena Foria; Rachele Messina; Elisabetta Peccol; Alessia Losa; Michele Fabro; Gianluca Gori; Pietro Zandigiacomo; Guido Cipriani; Raffaele Testolin (Genetic Resources and Crop Evolution, 2020)

Sex change in kiwifruit (Actinidia chinensis Planch.): a developmental framework for the bisexual to unisexual floral transition - Elisabetta Caporali; Raffaele Testolin; Simon Pierce; Alberto Spada (Plant Reproduction, 2019)

A RAD-based linkage map of kiwifruit (Actinidia chinensis Pl.) as a tool to improve the genome assembly and to scan the genomic region of the gender determinant for the marker-assisted breeding - Davide Scaglione; Alice Fornasiero; Catalina Pinto; Federica Cattonaro; Alessandro Spadotto; Rodrigo Infante; Claudio Meneses; Rachele Messina; Orietta Lain; Guido Cipriani; Raffaele Testolin (Tree Genetics & Genomes, 2015)

Selective sweep at the Rpv3 locus during grapevine breeding for downy mildew resistance - Gabriele Di Gaspero; Dario Copetti; Courtney Coleman; Simone Diego Castellarin; Rudolf Eibach; Pál Kozma; Thierry Lacombe; Gregory Gambetta; Andrey Zvyagin; Petar Cindrić; László Kovács; Michele Morgante; et al. (Theoretical and Applied Genetics, 2012)

Defence responses in Rpv3-dependent resistance to grapevine downy mildew - Karen Casagrande; Luigi Falginella; Simone Diego Castellarin; Raffaele Testolin; Gabriele Di Gaspero (Planta, 2011)

The SSR-based molecular profile of 1005 grapevine (Vitis vinifera L.) accessions uncovers new synonymy and parentages, and reveals a large admixture amongst varieties of different geographic origin - Guido Cipriani; Alessandro Spadotto; Irena Jurman; Gabriele Di Gaspero; Manna Crespan; Stefano Meneghetti; Enrica Frare; Rita Vignani; Mauro Cresti; Michele Morgante; Mario Pezzotti; Enrico Pe; et al. (Theoretical and Applied Genetics, 2010)

Resistance to Plasmopara viticola in grapevine ‘Bianca’ is controlled by a major dominant gene causing localised necrosis at the infection site - Diana Bellin; Elisa Peressotti; Didier Merdinoglu; Sabine Wiedemann-Merdinoglu; Anne-Françoise Adam-Blondon; Guido Cipriani; Michele Morgante; Raffaele Testolin; Gabriele Di Gaspero (Theoretical and Applied Genetics, 2009)

Resistance to Erysiphe necator in the grapevine ‘Kishmish vatkana’ is controlled by a single locus through restriction of hyphal growth - Sarolta Hoffmann; Gabriele Di Gaspero; László Kovács; Susanne Howard; Erzsébet Kiss; Zsuzsanna Galbács; Raffaele Testolin; Pál Kozma (Theoretical and Applied Genetics, 2008)